The path of pre-ribosomes through the nuclear pore complex revealed by electron tomography - Franck Delavoie (Nature Portfolio, 2019)
Large protein complexes and ribonucleoprotein particles (RNPs) such as pre-ribosomes are transported from the nucleus to the cytoplasm through the nuclear pore complex (NPC). Here the authors use ultrafast freezing and electron tomography to catch snapshots of native RNPs crossing the NPC and estimate their transit time using a probabilistic model.